2022
DOI: 10.1016/j.scitotenv.2021.150327
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee (Apis mellifera L.) colonies as bioindicators of environmental SARS-CoV-2 occurrence

Abstract: SARS-CoV-2 is responsible for the COVID-19 pandemic. Airflows sustain the infection spread, and in densely urbanized areas airborne particulate matters (PMs) are deemed to aggravate the viral transmission. Apis mellifera colonies are used as bioindicators as they allow environmental sampling of different nature, PMs included. This experiment demonstrates for the first time the possible use of honey bee colonies in the SARS-CoV-2 monitoring. The trial was conducted in Bologna o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 88 publications
4
9
0
Order By: Relevance
“…Since in farm animals such as buffaloes, goats, sheep, horses, rabbits, hens, pigs, or cows, SARS-CoV-2 has not been detected despite contact with their infected breeders [44], we can exclude the contamination of samples from operators' coughing and sneezing or from the passage of fomites to honey bees, and the environmental contamination of honey bees must be assumed. So, in accordance with other studies [35,45], our results showed that in the future, honey bees could very likely be used as indicators of outbreaks of airborne pathogens. Furthermore, by providing evidence that the molecular characterization of the pathogens detected in honey bee samples is also technically feasible, this study opens the possibility of using this approach for the identification and mapping of emerging diseases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Since in farm animals such as buffaloes, goats, sheep, horses, rabbits, hens, pigs, or cows, SARS-CoV-2 has not been detected despite contact with their infected breeders [44], we can exclude the contamination of samples from operators' coughing and sneezing or from the passage of fomites to honey bees, and the environmental contamination of honey bees must be assumed. So, in accordance with other studies [35,45], our results showed that in the future, honey bees could very likely be used as indicators of outbreaks of airborne pathogens. Furthermore, by providing evidence that the molecular characterization of the pathogens detected in honey bee samples is also technically feasible, this study opens the possibility of using this approach for the identification and mapping of emerging diseases.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, it was observed that honey bee colonies have a higher sample capacity than an automatic environmental monitoring station, because the honey bee body has a maximum diameter of 4.5 mm [46,47], and considering that one forager may leave the hive twenty times per day flying each time for 500 m [48], it can be said that even one single honey bee can come in contact with an approximate daily volume of air of 0.16 m 3 [49][50][51]. Assuming that in a colony there are 2000 foragers [49][50][51], those last bees may encounter 318 m 3 of air per day, from which airborne PMs may be sampled using their hairs and brought to the colony, Test period 0 500,000 1,000,000 1,500,000 2,000,000 So, in accordance with other studies [35,45], our results showed that in the future, honey bees could very likely be used as indicators of outbreaks of airborne pathogens. Furthermore, by providing evidence that the molecular characterization of the pathogens detected in honey bee samples is also technically feasible, this study opens the possibility of using this approach for the identification and mapping of emerging diseases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A recently conducted study in Italy showed that SARS-CoV-2 could be detected in the particulate matter carried by honey bee foragers, in this study foraging honey bees were positive for the target genes of viral SARS-CoV-2 RNA when coming back to the colony (Cilia et al 2022 ).…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, metagenomic data can be mined for human-health related information [ 59 ]. Future uses of data collected in this manner could be assessment of antibiotic resistance gene profiles, and while the molecular and computational methods used here were based on DNA analysis, it is possible they could be used to monitor RNA-based viruses such as Sars-Cov-2 or other future airborne pathogens, as demonstrated by targeted analyses using swab-based collection at hive doors during the COVID19 global pandemic [ 60 ].…”
Section: Discussionmentioning
confidence: 99%